2013
DOI: 10.1002/cncr.27917
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of epothilone B analog BMS‐247550 (NSC 710428) in patients with relapsed aggressive non‐Hodgkin lymphomas

Abstract: BACKGROUND The management of relapsed aggressive lymphomas remains problematic. Ixabepilone (BMS-247550, epothilone B analog), a potent inhibitor of tubulin disassembly, has promising preclinical and early-phase clinical activity in drug-resistant malignancies. METHODS This multicenter phase 2 clinical trial tested the activity and safety of ixabepilone in relapsed/refractory aggressive lymphoma patients with either chemosensitive (at least a partial response [PR] to most recent chemotherapy) or chemoresista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In recent years, macrocycles have emerged as one of the most promising categories of drug candidates for multiple indications. Macrocyclic systems are restricted in their rotational and conformational freedom. While this property is actively exploited in the design of highly effective and specific compounds, the interdependency of rotatable bonds and other features such as bridged rings pose significant challenges to conformer ensemble generation.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, macrocycles have emerged as one of the most promising categories of drug candidates for multiple indications. Macrocyclic systems are restricted in their rotational and conformational freedom. While this property is actively exploited in the design of highly effective and specific compounds, the interdependency of rotatable bonds and other features such as bridged rings pose significant challenges to conformer ensemble generation.…”
Section: Resultsmentioning
confidence: 99%
“…A total of uninformative 11 trials were found, 7 for lack of appropriate follow-up, 4 for accrual failure and 0 for duplicity. 22,26,32,46,49,53,61,65,66,74,76 These trials represent 792 patients and 226 patient-years of involvement in which there was a minimum of 208 grade 3–4 severe adverse events (27.8%, 95% CI 22.4%–33.9%) and 7 deaths occurred (1.4%, 95% CI 0.8%– 2.7%). Among these patients, 175 experienced objective tumour response (24%, 95% CI 16.7%– 33.3%).…”
Section: Resultsmentioning
confidence: 99%
“…rituximab, which became available soon after this study was started). 46 A nonpositive phase 2 trial of soft tissue sarcoma included a subgroup of 8 responding patients with leiomyosarcoma. 18 This was followed by a trial in uterine leiomyosarcoma; the study was nonpositive and had lower response rate than the first trial.…”
Section: Discussionmentioning
confidence: 99%
“…Ixabepilone was well-tolerated, except for neuropathic toxicity. Considering that the response rate of ixabepilone is modest compared to other drugs currently in use, its use in lymphomas is very limited (Churpek, et al, 2013).…”
Section: Epothilonesmentioning
confidence: 99%